Evidence for diabatic cooling and poleward transport within and around the 1987 Antarctic ozone hole - Profitt, M. H.; Kelly, K. K.; Powell, J. A.; Gary, B. L.; Loewenstein, M.; Podolske, J. R.; Strahan, S. E.; Chan, K. R. (1989)
Atmospheric dynamics at altitudes of 17.5-19 km were analyzed using measurements of N2O, total water, total odd-nitrogen species, and potential vorticity (derived from pressures, temperatures, and wind speeds) obtained aboard the ER-2 aircraft flown in the period between August 23 and September 22 during the Airborne Antarctic Ozone Experiment. Results indicated a consistent gradual poleward movement of air, extending from about 10 deg in latitude outside the boundary of the ozone hole to about 5 deg inside. Evidence is presented of ongoing diabatic cooling throughout this zone, both inside and outside the chemically perturbed region.